Preparation method and application of water-based flexible electrode capable of being used for loading large-molecular-weight active material
By removing Al from the MAX-phase ceramic of Ti3AlC2, Ti3C2Tx Mxene was prepared, and composited with macromolecular active materials, combined with bacterial cellulose as the base material, the problem that water-based flexible electrodes are difficult to load active materials with a large molecular weight is solved, and the preparation of high-performance flexible electrodes was achieved.
Patent Information
- Application Number
- CN202411703360.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-26
AI Technical Summary
The prior art is difficult to load water-based flexible electrodes with large molecular weight active materials, resulting in insufficient material performance.
By removing Al from the MAX-phase ceramic of the layered compound Ti3AlC2, Ti3C2Tx Mxene was prepared, and composited with polyanionic and Prussian-like macromolecular active materials, combined with bacterial cellulose as the base material, a flexible electrode with high mechanical properties and good conductive network was prepared.
It achieves large load capacity and high area specific capacity, and exhibits good rate performance, and is cheap at the same time, simple process operation, and is suitable for large-scale production.
Smart Images

Figure CN119601574A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage materials, and in particular relates to a preparation method and application of a water-based flexible electrode that can be used to load active materials with a relatively large molecular weight. Background Art
[0002] Energy is an important foundation for national security and sustainable development of the national economy. Lithium-ion batteries are the most representative electrochemical energy storage devices. However, the safety hazards of lithium-ion batteries, insufficient lithium resources, and uneven geographical distribution have limited their application in further large-scale commercial energy storage. Therefore, more and more researchers are focusing on the development of rechargeable and dischargeable ion batteries such as sodium ions and potassium ions as alternative energy storage devices to lithium-ion batteries. At present, wearable electronic products have been rapidly developed, such as wearable multimedia devices, flexible sensors, and implantable medical electronic devices. In order to meet this demand, energy supply components must be non-toxic, flexible, lightweight, have high mechanical strength and good biocompatibility. The emergence of aqueous sodium and potassium ion batteries provides a feasible solution to the safety problems of batteries based on organic systems. In high-performance flexible devices, flexible electrodes are undoubtedly the most important components, and researchers are urgently needed to conduct systematic, in-depth, and comprehensive research and development on the preparation technology of flexible electrodes. However, looking at both China and abroad, the research and development level of flexible electrodes for aqueous sodium-ion batteries is very low. The reasons are multifaceted, among which the lack of suitable substrate materials is particularly prominent, especially the lack of substrate materials that can be used for larger molecular weight active materials such as polyanions and Prussian blue-like materials. Therefore, the development of new high-performance substrate materials is the key to promoting the development of aqueous flexible sodium-ion batteries. At the same time, the intrinsic conductivity of larger molecular weight active materials such as polyanions and Prussian blue-like materials is low, which also limits the full performance of the material properties. Therefore, constructing a flexible substrate with both high mechanical properties and a good conductive network is one of the key conditions for improving the overall performance of aqueous flexible sodium-ion batteries. Summary of the invention
[0003] The purpose of the present invention is to solve the problem that the existing aqueous flexible electrodes are difficult to load large molecular weight active materials, and to provide a preparation method and application of an aqueous flexible electrode that can be used to load large molecular weight active materials.
[0004] The present invention provides a method for preparing an aqueous flexible electrode that can be used to load an active material with a relatively large molecular weight. The method is carried out according to the following steps:
[0005] 1. Using HF as an etchant, Al was removed from the MAX phase ceramic of the layered compound Ti3AlC2, and then the product was washed and collected, and mechanically peeled off to prepare Ti3C2T x Mxene;
[0006] 2. Treating the surface of the polyanionic and Prussian blue-like macromolecular active materials for energy storage or the carbon-coated and doped composite materials based on the polyanionic and Prussian blue-like macromolecular active materials for energy storage by using a sensitizer;
[0007] 3. The Ti3C2T obtained in step 1 x Dispersing Mxene in deionized water, adding the macromolecular active material treated in step 2, stirring and filtering to obtain a composite material, and dispersing the composite material in deionized water to obtain a composite material dispersion;
[0008] 4. dispersing the washed bacterial cellulose into deionized water, and then transferring it to a homogenizer for stirring to obtain a bacterial cellulose dispersion;
[0009] 5. adding the composite material dispersion prepared in step 3 to the bacterial cellulose dispersion to prepare a mixed slurry, and then preparing a flexible electrode by vacuum filtration and drying;
[0010] Alternatively, the bacterial cellulose dispersion is vacuum filtered and freeze-dried to obtain a bacterial cellulose membrane, and then the composite material dispersion is vacuum filtered into the bacterial cellulose membrane to prepare a flexible electrode.
[0011] The bacterial cellulose raw material is a block material or a film material.
[0012] Furthermore, the HF in step 1 is prepared by dissolving LiF in an aqueous solution of HCl, wherein the mass ratio of LiF to Ti3AlC2 is (0.2-10):1;
[0013] Furthermore, the etching conditions in step 1 are a temperature of 5 to 80° C., an etching time of 2 to 100 h, and the etching is performed under mechanical stirring.
[0014] Furthermore, the polyanionic and Prussian blue-like macromolecular active materials for energy storage described in step 2 are NaTi2(PO4)3, Na3V2(PO4)3, Na2CoFe(CN)6, Na2MnFe(CN)6, NaFePO4 or Na2FePO4F.
[0015] Furthermore, the sensitizer described in step 2 is a mixture of SnCl2 and HCl in a mass ratio of (0.2-10):1.
[0016] Furthermore, the sensitizer conditions described in step 2 are SnCl2 concentration of 0.005-1 mol / L and sensitization time of 0.1-5h.
[0017] Furthermore, in step 3, the active material and Ti3C2T x The mass ratio of Mxene is (0.1~20):1.
[0018] Furthermore, in step 4, the preparation conditions of the bacterial cellulose dispersion are a shear rate of 5000-20000 r / min and a treatment time of 1-60 min.
[0019] Furthermore, the mass ratio of the composite material in the composite material dispersion in step five to the bacterial fibers in the bacterial cellulose dispersion is (0.1-15):1.
[0020] The invention discloses an application of an aqueous flexible electrode which can be used for loading active materials with relatively large molecular weights. The flexible electrode is used in an aqueous flexible ion battery.
[0021] The aqueous flexible ion battery may be an aqueous flexible sodium ion battery.
[0022] The present invention has the following beneficial effects:
[0023] 1. Bacterial cellulose is a special fiber material produced by microorganisms. The special microstructure, high-strength mechanical properties and good hydrophilicity of bacterial cellulose can not only ensure the improvement of the electrochemical performance of flexible electrodes, but also help to improve the mechanical properties of flexible electrodes, making it more suitable as a supporting material for water-based flexible electrodes.
[0024] 2. Ti3C2T x MXene has good electronic conductivity, hydrophilicity, biocompatibility and large-sheet-size microstructure. It can not only effectively solve the defects of poor electronic conductivity of polyanionic and Prussian blue-type materials, but also is conducive to the subsequent design and preparation of flexible electrodes.
[0025] 3. The present invention constructs a flexible substrate with hydrophilicity, high mechanical properties and good conductive network, which can be used to load active materials with larger molecular weight, achieve large loading amount and obtain high area specific capacity, while showing good rate performance.
[0026] 4. Low cost, simple process operation, and can be produced on a large scale.
[0027] 5. It can be directly used as a flexible electrode for aqueous sodium-ion batteries and has good energy storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a front scanning electron microscope image of the flexible electrode prepared in Example 1;
[0029] Figure 2 This is a side scanning electron microscope image of the flexible electrode prepared in Example 1. DETAILED DESCRIPTION
[0030] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention more clearly understood, the spirit of the contents disclosed by the present invention will be described in detail below. After understanding the embodiments of the contents of the present invention, any technician in the relevant technical field can change and modify them according to the techniques taught by the contents of the present invention without departing from the spirit and scope of the contents of the present invention.
[0031] The exemplary embodiments of the present invention and the description thereof are used to explain the present invention, but are not intended to limit the present invention.
[0032] Example 1: This example provides a method for preparing a water-based flexible electrode that can be used to load active materials with a relatively large molecular weight and its application, which is carried out in the following steps:
[0033] First, 3.2g LiF was dissolved in 40mL 9M HCl aqueous solution, and then 2g Ti3AlC2 powder was added to the above LiF / HCl mixed solution and stirred at 40°C for 35h. Subsequently, the obtained solid product was washed four times with deionized water and centrifuged at 5000r / min until the pH value of the supernatant was close to neutralization. Finally, the sediment was dispersed in deionized water and ultrasonically treated for 2h, and then centrifuged at 5000r / min for 1h to collect the product.
[0034] 2. Prepare NaTi2(PO4)3 by solvothermal method. Specifically: Mix 0.56mL of 0.1mol / L potassium chloride solution with 140mL of ethanol, add 0.92g of hexadecylamine, and stir until the solid is completely dissolved. Then add an appropriate amount of titanium isopropoxide liquid, and add CH3COONa powder and H3PO4 solution according to the stoichiometric ratio, and stir for 2h. Then, in a reactor, react at 160°C for 3h, wash with deionized water and collect the product. Finally, sinter at 750°C for 4h under the protection of inert gas to obtain NaTi2(PO4)3.
[0035] 3. Using methanol and water (volume ratio = 1:1) as solvent, soak 200 mg NaTi2(PO4)3 in a mixed solution containing 0.03 M SnCl2 and 0.1 M HCl for 3 h, and collect the product after washing with deionized water.
[0036] 4. Add 60mg Ti3C2T x MXene was dispersed in deionized water, and 150 mg of NaTi2(PO4)3 active material treated in step 3 was added, stirred and filtered to prepare a composite material, and the composite material was dispersed in deionized water to obtain a composite material dispersion.
[0037] 5. Wash 1 g of bacterial cellulose raw material with deionized water, disperse it in deionized water, transfer it to a homogenizer and stir it at a high speed of 10,000 r / min for 5 minutes to obtain a bacterial cellulose dispersion.
[0038] 6. Measure 200 mL of bacterial cellulose dispersion (containing 30 mg of bacterial cellulose), take the composite material dispersion prepared in step 4 (containing 140 mg of composite material) and add it to the bacterial cellulose dispersion to prepare a mixed slurry, and then prepare a flexible electrode by vacuum filtration and drying.
[0039] 7. Cut the prepared flexible electrode into 4 cm 2 blocks and are directly used in aqueous flexible sodium-ion batteries.
[0040] The obtained flexible electrode material was tested. Figure 1 As shown in Figure 2, NaTi2(PO4)3 particles are uniformly loaded on Ti3C2T x MXene surface; such as Figure 2 As shown, NaTi2(PO4)3 and Ti3C2T x The composite material formed by MXene overlaps with each other in the bacterial cellulose matrix to form a three-dimensional porous microstructure. The electrochemical performance test shows that in aqueous sodium ion batteries, the discharge capacity can reach 1.12 mAh cm at a rate of 0.5C. -2 , the capacity retention rate is 58% at 50C rate.
[0041] Comparative Example 1:
[0042] This comparative example uses a composite material without bacterial cellulose as a research object.
[0043] 1. Steps 1 to 4 are consistent with those in Example 1.
[0044] 2. Take the composite material dispersion prepared in step 4 (containing 140 mg of the composite material), vacuum filter the composite material dispersion, and then dry it to obtain a sample.
[0045] 3. Cut the prepared sample into 4cm 2 blocks and are directly used in aqueous flexible sodium-ion batteries.
[0046] The obtained sample was tested and found to crack during bending and could not be used as a flexible electrode.
[0047] Comparative Example 2:
[0048] This comparative example uses uncompounded Ti3C2T x The NaTi2(PO4)3 active material of MXene was taken as the research object.
[0049] 1. NaTi2(PO4)3 active material was prepared according to step 2 in Example 1.
[0050] 2. Wash 1 g of bacterial cellulose raw material with deionized water, disperse it in deionized water, transfer it to a homogenizer and stir it at a high speed of 10,000 r / min for 5 minutes to obtain a bacterial cellulose dispersion.
[0051] 3. Measure 200 mL of bacterial cellulose dispersion (containing 30 mg of bacterial cellulose), add 100 mg of NaTi2(PO4)3 active material to the bacterial cellulose dispersion to prepare a mixed slurry, and then prepare a sample by vacuum filtration and drying.
[0052] 4. Cut the prepared sample into 4cm 2 blocks and are directly used in aqueous flexible sodium-ion batteries.
[0053] The obtained sample was tested. Although the sample had good mechanical properties, its electrochemical properties were extremely poor, especially at higher current density, it had no capacity.
[0054] Example 2: This example provides a method for preparing a water-based flexible electrode that can be used to load an active material with a relatively large molecular weight and its application, which is carried out according to the following steps:
[0055] 1. Steps 1 to 5 are the same as in Example 1
[0056] 2. Measure 300 mL of bacterial cellulose dispersion (containing 45 mg of bacterial cellulose), add the prepared composite material dispersion (containing 230 mg of composite material) into the bacterial cellulose dispersion to prepare a mixed slurry, and then prepare a flexible electrode by vacuum filtration and drying.
[0057] 3. Cut the prepared flexible electrode into 4cm 2 blocks and are directly used in aqueous flexible sodium-ion batteries.
[0058] The obtained flexible electrode material was tested. The electrochemical performance test showed that in aqueous sodium ion batteries, the discharge capacity at 0.5C rate can reach 1.72mAh cm -2 , the capacity retention rate is 52% at 50C rate.
[0059] Example 3: This example provides a method for preparing a water-based flexible electrode that can be used to load an active material with a relatively large molecular weight and its application, which is carried out in the following steps:
[0060] First, 2g LiF was dissolved in 40mL 9M HCl aqueous solution, and then 2g Ti3AlC2 powder was added to the above LiF / HCl mixed solution and stirred at 40°C for 35h. Subsequently, the obtained solid product was washed four times with deionized water and centrifuged at 4000r / min until the pH value of the supernatant was close to neutralization. Finally, the sediment was dispersed in deionized water and ultrasonically treated for 3h, and then centrifuged at 4000r / min for 1h to collect the product.
[0061] 2. Using methanol and water (volume ratio = 1:1) as solvent, soak 300 mg of purchased Na4CoFe(CN)6 in a mixed solution containing 0.035MSnCl2 and 0.1M HCl for 2 h, and collect the product after washing with deionized water.
[0062] 4. Add 50mg Ti3C2T x MXene was dispersed in deionized water, and 160 mg of Na4CoFe(CN)6 active material treated in step 3 was added, stirred and filtered to prepare a composite material, and the composite material was dispersed in deionized water to obtain a composite material dispersion.
[0063] 5. Wash 1 g of bacterial cellulose raw material with deionized water, disperse it in deionized water, transfer it to a homogenizer and stir it at a high speed of 15000 r / min for 10 min to obtain a bacterial cellulose dispersion.
[0064] 6. Measure 300 mL of bacterial cellulose dispersion (containing 45 mg of bacterial cellulose), add the composite material dispersion (containing 200 mg of composite material) prepared in step 4 into the bacterial cellulose dispersion to prepare a mixed slurry, and then prepare a flexible electrode by vacuum filtration and drying.
[0065] 7. Cut the prepared flexible electrode into 4 cm 2 blocks and are directly used in aqueous sodium-ion batteries.
[0066] The obtained flexible electrode material was tested. The electrochemical performance test showed that in aqueous sodium ion batteries, the discharge capacity at 0.5C rate can reach 1.24 mAh cm -2 , the capacity retention rate is 51% at 50C rate.
Claims
1. A method for preparing an aqueous flexible electrode that can be used to load active materials with a relatively large molecular weight, characterized in that: The method proceeds as follows:
1. Using HF as an etchant, Al was removed from the MAX phase ceramic of the layered compound Ti3AlC2, and then the product was washed and collected, and mechanically peeled off to prepare Ti3C2T x Mxene; 2. Treating the surface of the polyanionic and Prussian blue-like macromolecular active materials for energy storage or the carbon-coated and doped composite materials based on the polyanionic and Prussian blue-like macromolecular active materials for energy storage by using a sensitizer; 3. The Ti3C2T obtained in step 1 x Dispersing Mxene in deionized water, adding the macromolecular active material treated in step 2, stirring and filtering to obtain a composite material, and dispersing the composite material in deionized water to obtain a composite material dispersion; 4. dispersing the washed bacterial cellulose into deionized water, and then transferring it to a homogenizer for stirring to obtain a bacterial cellulose dispersion; 5. adding the composite material dispersion prepared in step 3 to the bacterial cellulose dispersion to prepare a mixed slurry, and then preparing a flexible electrode by vacuum filtration and drying; Alternatively, the bacterial cellulose dispersion is vacuum filtered and freeze-dried to obtain a bacterial cellulose membrane, and then the composite material dispersion is vacuum filtered into the bacterial cellulose membrane to prepare a flexible electrode.
2. The method for preparing a water-based flexible electrode that can be used to load active materials with a relatively large molecular weight according to claim 1, characterized in that: The HF described in step 1 is prepared by dissolving LiF in an aqueous solution of HCl, wherein the mass ratio of LiF to Ti3AlC2 is (0.2-10):
1.
3. The method for preparing a water-based flexible electrode that can be used to load active materials with a relatively large molecular weight according to claim 1, characterized in that: The etching conditions in step 1 are a temperature of 5 to 80° C., an etching time of 2 to 100 h, and the etching is performed under mechanical stirring.
4. The method for preparing a water-based flexible electrode that can be used to load active materials with a relatively large molecular weight according to claim 1, characterized in that: The polyanionic and Prussian blue-type macromolecular active materials for energy storage described in step 2 are NaTi2(PO4)3, Na3V2(PO4)3, Na2CoFe(CN)6, Na2MnFe(CN)6, NaFePO4 or Na2FePO4F.
5. The method for preparing a water-based flexible electrode that can be used to load active materials with a relatively large molecular weight according to claim 1, characterized in that: The sensitizer described in step 2 is a mixture of SnCl2 and HCl in a mass ratio of (0.2-10):
1.
6. A method for preparing an aqueous flexible electrode that can be used to load active materials with a relatively large molecular weight according to claim 1 or 5, characterized in that: The sensitizer conditions described in step 2 are SnCl2 concentration of 0.005 to 1 mol / L and sensitization time of 0.1 to 5 h.
7. The method for preparing a water-based flexible electrode that can be used to load active materials with a relatively large molecular weight according to claim 1, characterized in that: In step 3, the active material and Ti3C2T x The mass ratio of Mxene is (0.1~20):
1.
8. The method for preparing an aqueous flexible electrode that can be used to load active materials with a relatively large molecular weight according to claim 1, characterized in that: The preparation conditions of the bacterial cellulose dispersion in step 4 are a shear rate of 5000-20000 r / min and a treatment time of 1-60 min.
9. The method for preparing a water-based flexible electrode that can be used to load active materials with a relatively large molecular weight according to claim 1, characterized in that: The mass ratio of the composite material in the composite material dispersion liquid described in step five to the bacterial fibers in the bacterial cellulose dispersion liquid is (0.1-15):
1.
10. Use of an aqueous flexible electrode for loading active materials with a relatively large molecular weight prepared according to any one of claims 1 to 9, characterized in that: The flexible electrode is used in an aqueous flexible ion battery.
Citation Information
Patent Citations
Preparation method and application of N-P-dopted carbon fiber / graphene / bacterial cellulose conducting film material
CN105609324A
Preparation method for carbon fiber reinforced aluminum-based boron carbide neutron shielding material
CN109680227A
Prussian blue analog / MXene composite electrode material and in-situ preparation method and application thereof
CN110783536A
Stretchable electrode and preparation method and application thereof
CN118676316A